Assessment of functional disorders of the upper limb in individuals with carpal tunnel syndrome - Бісмак, Олена (Slobozhanskyi Herald of Science and Sport, 2019)
Olena Bismak Carpal tunnel syndrome is the most common form of compression-ischemic neuropathy, found in clinical practice. Purpose: to evaluate functional disorders of the upper limb in individuals with carpal tunnel syndrome using the Boston questionnaire (Boston Carpal Tunnel Questionnaire, BCTQ). Material & Methods: analysis and synthesis of data from scientific and methodological literature and the Internet information network were used; survey, medical history, mathematical methods. To assess the functional state of the affected upper limb during the initial examination, we used the Boston Carpal Tunnel Questionnaire (BCTQ), which consists of two scales: the Symptom Severity Scale (SSS) and the Function Status Scale (FSS), which was filled by the patient on his own. The study was conducted on the basis of the Kiev City Clinical Hospital No. 4 in the period from 2017 to 2018. The study involved 37 patients with CTS, of which 21 – women (56,8%) people, 16 – men (43,2%) people. Results: analyzed pain and sensory disorders on the scale of symptom severity (Symptom Severity Scale, SSS) and functional disorders on the scale (Function Status Scale, FSS) of the Boston questionnaire. During the initial examination of patients with CTS, we found that mainly moderate (24,3%) and severe pain (37,8%) in the affected upper limb prevailed in patients, which over the past 2 weeks led patients to wake up at night: 1 time – 32,4% of patients, 2–3 times – 29,7% of people. During the day, 29,7% of patients complained of moderate pain in the arm and 43,3% of people were worried about severe pain. Most patients (48,7%) indicated that pain lasts from 10 minutes to 60 minutes. For functional disorders, the greatest difficulties for patients occurred when fastening buttons on clothes – 83,8%, opening a bottle – 86,5% and doing homework – 79,9% of people. Conclusion: an initial examination of patients with carpal tunnel syndrome indicated pain in the affected limb, numbness, decreased sensitivity, muscle weakness on the severity scale of the symptoms of the Boston questionnaire were observed. On the scale of functional impairment, we found difficulties that arose in patients performing everyday activities and self-care.